Effects of sodium metabisulphite and blanching pretreatments on the quality characteristics of yam bean (Pachyrhizus erosus) flour - Buckman, E.S.; Plahar, W.A.; Oduro, I.N.; Carey, E.E. (Sciencedomain International, 2015)
Aims. To determine the effects of sodium metabisulphite and blanching pretreatments on the quality characteristics of yam bean (Pachyrhizus erosus) flour. Study Design: Evaluation of the effects of peeling, blanching and sodium metabisulphite pretreatments on the ease of drying, particle size distribution, colour and pH of yam bean flour using a 2 x 3 factorial design. Place and Duration of Study: Yam bean roots were obtained from the CSIR-Crops Research Institute, Kumasi, Ghana. All reagents used were obtained from accredited suppliers in Accra, Ghana. Actual experimental studies were conducted at the laboratories of the CSIR-Food Research Institute, Accra, Ghana, between August 2012 and November 2013. Methodology. We subjected peeled and unpeeled yam bean tubers (Pachyrhizus erosus) to three pretreatments involving blanching at 100 C for 3 min; soaking in 0.1% sodium metabisulphite solution for 3 min and no treatment control. Samples were dried at 55 C for 6 hours, cooled to room temperature, milled, sieved and the flour analyzed for ease of drying as indicated by the final moisture content, colour, pH, and ease of milling as indicated by particle size distribution. Results: The pretreatment methods had significant (p>0.05) effects on the colour of the flour samples. Peeling, followed by sodium metabisulphite pretreatment produced whitest yam bean flour (L-value of 90.89). Flour samples from unpeeled roots recorded lower pH (p>0.05) than those from peeled samples. The combined effects of peeling and sodium metabisulphite or blanching pretreatments produced flours with desirable pH values. The blanched sample had coarser particles (50%>100 <my>m) compared to the no treatment control and sodium metabisulphite treated flours (30%>100 <my>m). Peeling, metabisulphite or blanching pretreatments did not affect the rate of drying significantly as indicated by their final moisture values. Conclusion: A standard procedure for yam bean flour production has been suggested to include peeling and sodium metabisulphite pretreatment